A Fortran visualization program for spherical data on a Yin‐Yang grid. (23rd April 2014) - Yoshida, Masato; Kageyama, Akira
Abstract A Fortran 90 program to visualize data on the Yin‐Yang grid system is developed. The purpose of this study is to provide simulation researchers with a source code as a starting point of their own custom‐made visualization tools. A basic but sufficiently diverse set of visualization methods are implemented using a Fortran 90 binding for OpenGL for scalar and vector fields defined or simulated on the Yin‐Yang grid.